lqlim o’zgarishining tog’li hududlarga ta’siri - Nasvaliyeva Gulnozaxon To'lqinjonovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article analyzes the impact of climate change on mountainous regions. It discusses rising temperatures, glacier melting, ecosystem changes, and the effects on local populations. The research findings highlight environmental issues in mountainous areas and provide recommendations for mitigating these challenges.